Promoção da saúde na escola: das possibilidades e barreiras em meio a violência e ao sofrimento social - Piccoli, Luiza Machado (Universidade do Vale do Rio dos Sinos, 2016)
The following research is dedicated to explore the relationship between the speeches of a Porto Alegre’s public system school teachers, and the social context in which they are inserted. The aim is to understand how the educators’ views about the students, the families and the community are related with the docent possibilities of teaching and promoting health in the school environment. The nature of the following study is qualitative and it is accomplished from the data compilation through semistructured individual interviews, active observation and focus group. The discussion of the results is carried out through content analysis divided into two distinct thematic categories that consider the discourses from the perspective of violence and of social suffering, and health promotion opportunities at school. It shows the existence of a complex social reality contextualized by socioeconomic data and an environmental historical rescue in which the research object is inserted. It embraces the strategies identified by teachers to promote health in the school environment taking into account the social dimension based on territoriality, showing the imperative consideration of social suffering and symbolic violence to analyze the results. It is considered the health promotion in school in direct connection with the construction of possibilities of expansion of freedom and autonomy. It is concluded the need to develop spaces of transversal and Intersectoral action for health promotion, resulting in commitment and community empowerment.
Keywords: Promoção da saúde; Escola; Professor; Alunos; Famílias; Health promotion; School; Teacher; Students; Families; ACCNPQ::Ciências da Saúde::Saúde Coletiva